2018
DOI: 10.15850/ijihs.v6n2.1378
|View full text |Cite
|
Sign up to set email alerts
|

Ethanol Extract of Stylissa carteri Induces Cell Death in Parental and Paclitaxel-Resistant Cervical Cancer Cells

Abstract: Objective: To evaluate the cytotoxic effects of ethanol extract from marine sponge Stylissa carteri in both parental and paclitaxel-resistant HeLa cervical cancer cells. Methods: This was an experimental in-vitro study subjected ethanol extract from Stylissa carteri obtained from Pramuka Island, Kepulauan Seribu National Park, Jakarta. Both parental and paclitaxel-resistant HeLa cells were treated with ethanol extract followed by microscopic observation and MTT assay. The IC 50 and drug curves were analyzed us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…A previous study showed that the ethanol extract of Stylissa carteri was cytotoxic against cervical cancer cells (the IC 50 =1 μg/ml). 21 The findings above indicated that Stylissa carteri consisted of active compounds that could be potentially developed into potential candidates to reduce viability of some types of cancer.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…A previous study showed that the ethanol extract of Stylissa carteri was cytotoxic against cervical cancer cells (the IC 50 =1 μg/ml). 21 The findings above indicated that Stylissa carteri consisted of active compounds that could be potentially developed into potential candidates to reduce viability of some types of cancer.…”
Section: Discussionmentioning
confidence: 96%
“…19,20 The ethanol extract of Stylissa carteri has cytotoxic effects on several cancer cell lines, including luminal A, HER2 + and triple-negative type breast cancer cells, and cervical cancer cells. 21,22 To further purify compounds of Stylissa carteri and to obtain stronger potential of anticancer fraction, this study was conducted to explore effects on fraction levels, especially on the ethyl acetate fraction. This study aimed to determine the cytotoxic effects of ethyl acetate fraction of the Stylissa carteri on trastuzumabresistance HER2+ breast cancer cells, HCC-1954 in vitro through its cytotoxicity parameters using the 3-[4,5-dimethylthiazol-2-yl] -2.5 diphenyl tetrazolium bromide (MTT) assay and estimation of 50% inhibitory concentration (IC 50 ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, a recent study shows that the methanol crude extract of S. carteri has cytotoxic effects in cervical cancer HeLa cells (Dewi, 2017). Our previous data demonstrates that the Et(OH) extract of S. carteri triggers cell death in both parental HeLa cells and paclitaxel resistance HeLa cells (Hardani et al, 2018).…”
Section: Discussionmentioning
confidence: 98%
“…Species were visually identified in the field, and confirmed at Department of Marine Science and Technology, Faculty of Fisheries and Marine Sciences, Bogor Agricultural University. Samples were cut into small size and then extracted using maceration technic in ethanol according to previous study (Hardani et al, 2018).…”
Section: Extraction Of Stylissa Carterimentioning
confidence: 99%
“…The ethyl acetate fraction from ethanol extract Stylissa carteri was able to inhibit the activity of proteasome E2 (Ubc13) and the interactions between p53-MDM2 (E3) (Afifi, 2017). Our previous study showed the ethanol extract of Stylissa carteri has a cytotoxic effect in different BC cell lines including luminal A (MCF-7), HER2+ (SKBR3, HCC-1954) and TNBC (MDA MB 231), and also having an effect in cervical cancer cells (Hardani et al, 2018;Bashari et al, 2019). Moreover, it inhibits MDA MB 231 cell proliferation and migration (Bashari et al, 2019).…”
Section: Research Articlementioning
confidence: 99%